BENZEDEIRAS: A EDUCAÇÃO DE RESISTÊNCIA FEMININA DE MULHERES NEGRAS PELAS ERVAS - DIAS, MARCIA DENISE DE LIMA (2019)
The research points out the educational processes associated with self-care and care associated with the healing performance. In addition, it describes the traditional knowledge of healing taught and transmitted in Foz do Jordão county, Paraná State (Brazil), among generations’ time; and, possibly, such process happened through matricentral tradition (DIOP, 2015). Furthermore, it aimed on education processes related to healing which were perpetuated through a long period in the Foz Jordanian community. By that, we proposed to connect to such process Elda Rizzo de Oliveira’s (1985) concept of healing to Alain Caillé’s (2014) and Eric Saubourin’s (2008,2011) concept of reciprocity about the community attendance. According to the Educational Ethnography, observations and descriptions occurred from 2017 through 2018 on women healer’s practices and performances of herbs understanding. By describing and highlighting this traditional knowledge, Jefferson Olivatto da Silva’s (2016) learning constellations can, simultaneously, analyze and interconnect educational practices in the family and community routine of blessing. Sometimes, women healers maintained such millennial habit of herbs use being the only community health care. Furthermore, according to healing performance those healers aggregated learning constellations of prevention and health protection based on traditional knowledge, educational practices and traces of family and community learning. Whereby, the caring relationships by being a mother, being a woman and being a healer responded to the transmission of traditional knowledge. Learning traits were, intrinsically, linked to the daily life and the family and community experiences of these women, as well as present in the relations of maternal care of the family, maternal care with the other (care), matricentral construction of illness of body and spirit, as well as their mastery of herbs. To think of learning constellations enabled to understand how those healers perpetuated their knowledge in Foz do Jordão’s the community, because they are reflected in everyday life, so in family as consultants. It concludes that women healers develop affectivity and generosity as ethical relating values and teach how to aid others using herbs, to overcome sufferings and issues of bodily and spiritual health. Thus, learning constellations has demonstrated the performance cares about reciprocity principle based on, besides dedicating yourself to others, doing it for the sake of well-being, in as much as the women healers spread of their roots and teach the knowledge maintaining alive their practice.